Attitudes towards the use of information and communication technologies (ICT) at work: Findings from the health care sector in Greece - Vozikis, Athanassios; Ypofanti, Maria; Papadopoulos, Ioannis (SPOUDAI Journal of Economics and Business, 2010)
The aim of our study is to investigate the relationship between several demographic factors and the attitudes of personnel towards the use of Information and Communication Technologies (ICT) at work. Our random sample consisted of administrative, medical and nursing personnel from three Public Hospitals (total 223 employees), aged 39 (± 19). The data were collected using the following instruments: 1) Questionnaire of demographic elements and 2) Questionnaire «16-19 Computer Attitude’s Scale» as they were adjusted to fit the needs of this study. The research findings indicate that the employees who use ICT show more positive attitudes towards new technologies, possibly due to the fact that they understand the benefits that will exist for their work through a computerized information system. The new employees are more fa miliar with ICT technologies, while the more complex specialties consider the use of com puterized information systems important aid to make their work more effective, in contrast to older workers as well as employees who have received only primary education. JEL Classifications: I10, O32, C10.